Absenteeism and osteomuscular symptoms in technicians and nursing auxiliaries of hospital inpatient units - Luccas Melo de Souza; Eduarda Soriano Davila; Chirley Dias Scopel; Patrícia do Nascimento Amaral Barbieri (Revista de Enfermagem da Universidade Federal de Santa Maria, 2018)
Aim: to examine the relation between absenteeism and the musculoskeletal symptoms in nursing technicians and auxiliaries of adult inpatient units. Method: it is a cross-sectional, quantitative study, carried out with 71 technicians and auxiliary nurses of the adult inpatient units in a private hospital. The Nordic Musculoskeletal Questionnaire and analytical statistics were used. Results: of the subjects, 51.4% reported pain or paresthesia in the neck, shoulders and upper back region, in the last 12 months. In this period, 58% reported pain in the lower back region. Absenteeism was statistically higher (p<0,05) on workers who reported symptoms of pain/paraesthesia on the shoulders, elbows and lower back or who have stopped performing some activity due to symptoms in the neck or lower back, both in the last 12 months. Conclusion: the expansion of the studies on musculoskeletal diseases and absenteeism is fundamental to improve the working conditions in nursing.